Enhancing access to care in northern rural communities via telehealth. Issue 2 (28th January 2019) - Jong, Michael; Mendez, Ivar; Jong, Robert
ABSTRACT: The cost of providing health care in northern Canada is higher than the rest of Canada. Telehealth has the potential to reduce health care expenditures. Yet this is still underutilised in Canada and globally. This paper describes the services provided through telehealth in some northern regions of Canada. It provides recommendations on the requirements for setting up real presence telehealth and how utilisation can be enhanced. Telehealth offers potential benefits for health outcomes by increasing access to healthcare, and reducing expenditures.